2014
DOI: 10.1002/jts.21891
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Parents’ PTSD Severity and Children's Psychological Distress: A Meta‐Analysis

Abstract: The authors conducted a meta-analysis of studies on the correlation between parents' PTSD symptom severity and children's psychological status. An extensive search of the literature yielded 550 studies that were screened for inclusion criteria (i.e., parent assessed for PTSD, child assessed for distress or behavioral problems, associations between parent PTSD and child status examined). Sixty-two studies were further reviewed, resulting in a final sample of 42 studies. Results yielded a moderate overall effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
186
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(215 citation statements)
references
References 84 publications
20
186
2
Order By: Relevance
“…Perhaps unexpectedly, PTSD symptoms did not vary according to family type. However, this result concurs with the understanding that the severity, timing, and type of traumatic experiences are the most important determinants of the severity of PTSD (Lambert, Holzer, & Hasbun, 2014). …”
Section: Discussionsupporting
confidence: 88%
“…Perhaps unexpectedly, PTSD symptoms did not vary according to family type. However, this result concurs with the understanding that the severity, timing, and type of traumatic experiences are the most important determinants of the severity of PTSD (Lambert, Holzer, & Hasbun, 2014). …”
Section: Discussionsupporting
confidence: 88%
“…This study found that children of tortured parents had more symptoms of anxiety, depression, post-traumatic stress, attention deficits, and behavioral disorders compared with the control group. Finally a recent meta-analysis on the association between parents' PTSD severity and children's psychological distress, which included 42 samples found a moderate overall effect size r=.35, indicating that parental symptoms of PTSD influence children negatively (Lambert, Holzer, & Hasbun, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically disruptions in attachment representations (Almqvist & Broberg, 2003), intrafamily communication (Measham & Rousseau, 2010) and parental symptom level (Lambert et al, 2014) have all been proposed as potential mediating mechanisms. This paper seeks to identify potential risk and protective factors by examining the bivariate associations between intra-family communication style regarding the parents' traumatic experiences from the past with children's psychosocial adjustment and attachment security in a sample of traumatized Middle Eastern refugee families with children without a history of direct trauma exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Dekel and Goldblatt (2008), clinical observations and empirical research have shown that the consequences of traumatic events are not limited to the person immediately exposed to the event, and that they often affect family and friends. In a meta-analysis involving 42 studies, Lambert et al (2014) suggested the importance of considering the family context of the trauma survivors. Psychological problems of children with traumatized parents should be considered from the perspective of genetic predisposition, secondary traumatisation, difficulties in family functioning, or other challenges associated with living with a traumatized parent.…”
Section: Internalizing and Externalizing Problems In Children Of War mentioning
confidence: 99%